Democratic Republic of the Congo : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2014)
This Financial System Stability Assessment on the Democratic Republic of the Congo highlights that the Congolese financial sector has recovered from the crisis of 2009 but is at a crossroads. Although reforms have been initiated, the system remains shallow, highly dollarized, and characterized by balance sheet fragilities. The authorities have announced a de-dollarization process; however, greater progress on reforms to strengthen the financial system is needed to support financial deepening and economic growth. The team's analysis suggests that the financial system remains vulnerable. Resilience to shocks is undermined by the lack of risk-based supervision, lax regulation and weak enforcement of existing regulations, low profitability, and an excessive reliance on sight deposits. Steps are also needed to improve the capacity for micro- and macroprudential supervision. The implementation of risk-based supervision for individual banks is a critical prerequisite for effective crisis prevention. Assessments of bank-specific and systemic soundness are severely handicapped by weak supervisory data and other information gaps. There are significant weaknesses in accounting and auditing practices and, even if indicators suggest high capitalization levels, a more detailed analysis suggests banks are under-provisioned, partly owing to lax definitions of nonperforming loans and provisioning rules.